Analysis of X-ray whispering gallery waves propagating along liquid meniscuses; Resource-Efficient Technologies; No 1 - Goray L. I.; Asadchikov V. E; Roshchin B. S; Volkov Y. O; Tikhonov A. M (2018, 2018)
Title screen